Types And Level Of Indonesian-English Code-Mixing Used By Barbie Kumalasari On Boy William’svlog - Yokbeth Ester; Rahma Yanti; Yalmiadi Yalmiadi; Irsyad Shabri (LPPM Universitas Dharma Andalas, 2022)
This study analyses about types and levels of code-mixing used by Barbie Kumalasari on Boy William’s Vlog. This study refers to Hoffman’s theory in terms of types of code-mixing, and refers to Suwito’s theory in terms of levels of code-mixing. In achieving those objectives, the authors applied a descriptive qualitative approach. The authors implemented a qualitative method. The instrument of this study is document analysis. It focused on analysing and interpreting recorded documents. The findings showed that there are 46 data of types of code mixing, and 46 data of levels of code mixing. For the types of code-mixing, the highest data is intra-sentential code-mixing and the lowest type is intra-lexical code mixing. As for the levels of code-mixing, the highest data is in the word level and the lowest data are baster level and repetition word of code mixing.